PENANAMAN SIKAP PEDULI LINGKUNGAN PADA ANAK USIA DINI MELALUI MANAJEMEN SAMPAH KELUARGA - Galuh Kartikasari (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The environment is a place where human integration with nature should be well maintained. Awareness of environmental care needs to be instilled from an early age. Instilling caring for the environment can start from the family, which is the first place where children get education. This study aims to describe waste management in the family for instilling environmental care attitudes in early childhood. This research uses a qualitative approach with types of case study. The method and technique used are interview and observation. Primary data sources are in the form of two parents who have implemented waste management, and secondary data sources in the form of an early childhood aged 3.5 years. The results of the study stated that parents use organic waste as animal feed and natural fertilizer, then inorganic waste that can be recycled will be collected and sold. The attitude of caring for the environment that appears in children is understanding that garbage is thrown into the trash according to its type, understand that organic waste has benefits, and has an attitude that littering is not right.